An assessment of poplar integration in the farming system of Rupandehi district in Nepal - Bhandari, Krishna Bahadur; Upasena, Selawa H.; Suthad Setboonsarng; Suselo, Tri Binarko; Government of Denmark (Bangkok : Asian Institute of Technology, 1992)
People living in rural areas rely on farming. Existing farming system is of complex nature. The stability of the system depends on the interdependent balance between the sub-systems such as crop and livestock of which forests is an integral part. Given a lack of supply of inevitable forest products, a growing concern is to increase tree production at farm level. In this vein, Butwal Plywood Factory expanded poplar plantation activity to over come this situation in the Terai of Frnpandehi district. This study attempts to assess the success of the farm production systems, its benefiCiaries, the large, small or medium farmers. The findings reveal that the poplar program found useful for income generation in the long run. Although it competes with the cropping systems and has some influence in the management of their production system. It is also found that the economic benefit of poplar is much higher than that of the existing cropping systems. The program has focused mostly on large sized farmers of minority group, and they were motivated for the sake of land security and small to medium farmers have been little motivated due to their constraints of resources like land and irrigation. They are the group in majority who deserve maximum benefit by intensive use of land. The extension strategy used by the program was found to favour the rural rich. Thus, it was concluded that though the program was sucessful in the previous years but in the long run it should focus mostly on the medium and small farmers. Credit facility and price stability should be found to enable them to benefit from the poplar project.
Thesis (M. Sc.) - Asian Institute of Technology,1992
Keywords: Agricultural systems -- Nepal -- Rupandehi